Analisis Bentuk Desain Organisasi pada Sektor Bisnis, Pemerintahan, dan Pendidikan: Penelitian - Pungky Andriatama; Marcelina Ayu Vandini; Lidiya; Rony Edward Utama (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to identify the forms of organizational design applied, analyze their relevance to the needs and challenges of each institution, and provide recommendations for improvements based on theory and practice. This study uses a qualitative method with a descriptive-analytical approach. Data were obtained from scientific literature from the last 5 years (2020–2025), field studies, and previous research results relevant to organizational design, the business, government, and education sectors. The analysis was conducted by mapping influential internal and external factors, then linking them to contemporary organizational design theory. Based on the research results, it can be concluded that XL Axiata adopts a hybrid functional-divisional structure that supports operational scale and technical capabilities, but faces challenges of functional silos and cross-unit coordination in the digital era. The Secretariat General of the National Human Rights Commission (Komnas HAM) applies a functional bureaucratic structure appropriate for government organizations with the need for accountability and administrative efficiency. SMA Muhammadiyah 3 Jakarta has a collaborative hierarchical structure that supports the management of Islamic values-based education and adaptation to the independent curriculum.